Energy Management Without Iteration—A Regional Dispatch Event-Triggered Algorithm for Energy Internet - Tan, Jiaming (Frontiers in Energy Research, 2022)
Centralized algorithms and distributed algorithms have gained great attention in energy Internet nowadays. The centralized algorithm presses too much communication and numeration load to its control center in large-scale and neterogeny EI. The distributed algorithm requests too many times of iteration, and the performance and convergence speed is quite slow. The current literature presents a regional dispatch event-triggered algorithm (RDETA). Energy management in RDETA can transform between a centralized model and distributed model. With the effort, the energy management doesn't require iteration times in quantity. And due to event-triggered asynchronous communication, energy management not only doesn't rely on a global synchronous clock but also decreases communication frequency in most cases and increases communication frequency in exigency. In addition, RDETA adopts regional communication and regional energy dispatch, which can automatically modulate the scale of dispatch area by the degree of the energy problem. Finally, simulation results and theoretical demonstration show the contributions mentioned above of the proposed algorithm.